Artificial Intelligence-Based Virtual Tour for Vocational High Schools in Tourism Sector in Developing English Language Competence for Guides - Ramendra, Dewa Putu; Juniarta, Putu Adi Krisna; Parma, I Putu Gede; Jayanta, I Nyoman Laba; Tantri, Ade Asih Susiari; Dewantara, Kadek Andre Karisma (International Journal of Language Education, 2025)
This study aims to develop a virtual tour based on artificial intelligence for vocational high school students in the field of tourism in developing English language competencies for guides. This study contributes to the development of innovative technology-based learning media to improve the English language competence of vocational high school students in the field of tourism. This study adopts a design-based research approach utilizing the ADDIE instructional design model (Analysis, Design, Development, Implementation, and Evaluation). The data analysis in this study will employ both qualitative and quantitative methods. The findings of this study indicate a significant improvement in students' English language competence after using the Artificial Intelligence-Based Virtual Tour. The large effect size (Cohen’s d = 2.14) further confirms the strong impact of this intervention, demonstrating its effectiveness in improving students' abilities in English communication for guiding. The implementation of Artificial Intelligence (AI)-based Virtual Tour enables interactive simulations that resemble real-life situations in the tourism world, providing direct exposure for students to practice in a professional context. With the automatic evaluation and feedback features of AI, students can improve their language skills effectively, flexibly, and sustainably, making it a relevant approach to developing English language competency in the tourism sector.